Agent-Based Swarm Simulator for Extensions of Flocking Behavior Algorithms - Przemysław CZUBA; Rafał WRZOSEK (Communications of International Proceedings, 2021)
In recent years unmanned aerial vehicles (UAVs) proved themselves useful in a range of applications, where tasks are either too dangerous, costly, or dull for human workers. Many of such tasks are parallelizable in the context of agents performing the work which makes them easily horizontally scalable. To make it possible autonomous agents need to be coordinated among each other. Similar behavior can be observed in nature, where animals organize themselves in large groups. This paper proposes an agent-based swarm simulation test-bed for coordination algorithms based on flocking behaviors. We propose extensions for basic flocking algorithms and we demonstrate results from the developed simulator.
Keywords: Swarm Simulation; Multi-Agent Systems; Cooperation And Coordination; Autonomous Vehicles